Modular building intergraded solar-thermal flat plate hot air collectors - Kalogirou, Soteris A.; Florides, Georgios A.; Tsioutis, Charalambos; Christofi, Constantinos (My University, 2017)
In this paper three different constructions of integrated flat plate hot air collectors are build and tested. These types are: (a) integrated hot air collector utilising an aluminium foil duct (b) integrated hot air collector with internal metal separators and (c) integrated hot air collector with a mild steel square tube duct. The produced hot air can be circulated either directly in a room to raise its temperature or be blended with the air of a central Heating Ventilation and Air-Conditioning (HVAC) system to increase the temperature of the circulating air in winter. The collectors were tested in a day with no clouds. The solar radiation incident on the collector as well as the temperatures of the air at the collector inlet and outlet were recorded. The efficiency of the systems, defined as the ratio of the useful energy collected during the day over the total solar energy falling on the collector aperture during the same time, was estimated. The calculated maximum efficiency is considered as favourable with respect to existing solar collector systems. Specifically, the results show that collector type (a) gives a calculated maximum efficiency of 85%, type (b) 80% and type (c) 80%. The simplest and cheapest construction is that of type (a). All types of collectors tested can easily be mounted on a new or an existing wall (retrofitting) and the air duct can be supplied directly to individual rooms of the building or integrated together and coupled to a central unit.
Keywords: Hot air collectors; Integrated hot air collector; Aluminium foil duct; Internal metal separators